Recent advances of polymer acceptors for high-performance organic solar cells. Issue 1 (4th December 2019) - Zhao, Congcong; Wang, Jiuxing; Jiao, Jiqing; Huang, Linjun; Tang, Jianguo
Abstract : Recent advances in polymer acceptors that focus on structure–property relationships, which may provide guidance for photovoltaic materials, were systematically summarized. Abstract : In the past few decades, polymer solar cells (PSCs) have been intensively investigated in academic fields. The study of non-fullerene polymer acceptors has become a hot research focus due to their excellent opto-electronic properties such as wide light-absorbing ability, appropriate molecular energy levels, and easy chemical modifications. The much higher power conversion efficiencies (PCEs) of non-fullerene PSCs relative to fullerene PSCs revealed the significant potential of non-fullerene acceptors in PSCs. This review systematically summarizes the recent advancements of efficient polymer acceptors, including perylene diimide-based, naphthalene diimide-based, diketopyrrolopyrrole-based, double B←N bridged bipyridyl-based, and other polymer acceptors. Their structure–property relationships were thoroughly analyzed and summarized, which may provide new guidance for the rational structural design of high-performance photovoltaic materials.